Поняття, ознаки та класифікація злочинів у сфері економіки - Репчонок, А. Ю.; Repchonok, A. Yu. (Держава та регіони. Серія: Право. – 2020. – № 2 (68). – С. 278-284, 2020)
Розглянуто визначення та зміст поняття «злочини у сфері економіки», надано авторське бачення кола злочинів, що входять до цього поняття. Розкрито питання ознак злочинів у сфері економіки та співвідношення цього поняття із близькою категорією «економічні злочини». Наголошено про наявність кореляційних зв’язків між змістом поняття «злочини у сфері економіки» та процесу доказування по тим злочинам, що охоплюються цим поняттям. Запропоновано авторську класифікацію злочинів у сфері економіки.

The article examines the definition and content of the concept of “crimes in the economic sphere”, provides the author’s vision of the range of crimes included in this concept in view of modern theoretical provisions on this issue in the science of criminology and the provisions of the Special Part of the Criminal Code of Ukraine. The paper also discusses the issue of signs of crimes in the field of economy and the relationship of this concept with the close category of “economic crimes”. It is emphasized that there are correlations between the meaning of the concept of “crimes in the sphere of economy” and the process of proving the crimes covered by this concept. It was determined that the concept of crimes in the sphere of economy is very voluminous. The crimes included in this concept are diverse in terms of their criminal-legal structure: they differ both in terms of objective and subjective characteristics, although they are in a dialectical relationship. The specified feature of this system directly affects the further study of the order of proof during their investigation, which requires the search for common patterns in the sources of evidence, means of proof, the order of collection, research and evaluation of evidence during criminal proceedings for these categories of crimes. Based on the results of the research, the author’s classification of crimes in the economic sphere is proposed, based on the previously mentioned conclusions and provisions of the Special Part of the Criminal Code of Ukraine. The specified criminal offenses are mostly provided for in the following sections of the Special Part of the Criminal Code of Ukraine: 1) criminal offenses against electoral, labor and other personal rights and freedoms of a person and citizen (Chapter V of the Criminal Code of Ukraine); 2) criminal offenses against property (Chapter VI of the Criminal Code of Ukraine); 3) criminal offenses in the field of economic activity (Chapter VII of the Criminal Code of Ukraine); 4) criminal offenses against the environment (Chapter VIII of the Criminal Code of Ukraine); 5) criminal offenses against production safety (Chapter X of the Criminal Code of Ukraine); 6) criminal offenses in the sphere of circulation of narcotic drugs, psychotropic substances, their analogues or precursors and other criminal offenses against public health (Chapter XIII of the Criminal Code of Ukraine); 7) criminal offenses in the sphere of protection of state secrets, inviolability of state borders, provision of conscription and mobilization (Chapter XIV of the Criminal Code of Ukraine); 8) criminal offenses in the field of use of electronic computing machines (computers), systems and computer networks and telecommunication networks (Chapter XVI of the Criminal Code of Ukraine); 9) criminal offenses in the field of official activity and professional activity related to the provision of public services (Chapter XVII of the Criminal Code of Ukraine).

Рассмотрено определение и содержание понятия «преступления в сфере экономики», предоставлено авторское видение круга преступлений, входящих в это понятие. Раскрыты вопросы признаков преступлений в сфере экономики и соотношение этого понятия с близкой категорией «экономические преступления». Отмечено наличие корреляционных связей между содержанием понятия «преступления в сфере экономики» и процесса доказывания по тем преступлениям, которые охватываются этим понятием. Предложена авторская классификация преступлений в сфере экономики.
Concept, signs and classification of crimes in the sphere of economy
Keywords: злочини у сфері економіки; crimes in the field of economy; преступления в сфере экономики; економічні злочини; economic crimes; экономические преступления; класифікація злочинів; classification of crimes; классификация преступлений; Україна; Ukraine; Украина; доказування; proving; доказывание